On the first approximation of the K-harmonics method - Alcarás, J. A. Castilho (AIP Publishing, 1977)
Formulas for the calculation of two-body central interactions in the first approximation of the K-harmonics method are presented. These formulas are exact and account for diagonal and off-diagonal matrix elements as well. © 1978 American Institute of Physics.